2017
DOI: 10.1016/j.cct.2017.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Design and implementation of a factorial randomized controlled trial of methadone maintenance therapy and an evidence-based behavioral intervention for incarcerated people living with HIV and opioid dependence in Malaysia

Abstract: Incarcerated people living with HIV and opioid dependence face enormous challenges to accessing evidence-based treatment during incarceration and after release into the community, placing them at risk of poor HIV treatment outcomes, relapse to opioid use and accompanying HIV transmission risk behaviors. Here we describe in detail the design and implementation of Project Harapan, a prospective clinical trial conducted among people living with HIV and opioid dependence who transitioned from prison to the communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 76 publications
(89 reference statements)
0
27
0
Order By: Relevance
“…With MARIC data stored and governed by data custodians across 11 countries, and ethical and cross-jurisdictional data-sharing restrictions preventing the direct sharing of individual-level data [ 43 ], the two-step IPDM-A methodology overcomes these barriers and permits data analysis across all data sources in the Consortium. To account for participant overlap between cohorts – for example, there is a small degree of overlap between the Rosen [ 34 ] and Ranapurwala [ 44 ] cohorts from the US, and also some overlap between the Dolan [ 24 ], Degenhardt [ 22 ] and Karaminia [ 29 ] cohorts from Australia – we will ensure that all participants, person-time and deaths are only included once prior to conducting any data analysis.…”
Section: Discussionmentioning
confidence: 99%
“…With MARIC data stored and governed by data custodians across 11 countries, and ethical and cross-jurisdictional data-sharing restrictions preventing the direct sharing of individual-level data [ 43 ], the two-step IPDM-A methodology overcomes these barriers and permits data analysis across all data sources in the Consortium. To account for participant overlap between cohorts – for example, there is a small degree of overlap between the Rosen [ 34 ] and Ranapurwala [ 44 ] cohorts from the US, and also some overlap between the Dolan [ 24 ], Degenhardt [ 22 ] and Karaminia [ 29 ] cohorts from Australia – we will ensure that all participants, person-time and deaths are only included once prior to conducting any data analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The association between incarceration and MMT discontinuation has also been well-described elsewhere, and qualitative studies suggest this may be due to barriers to MMT continuity during transitions between custodial and community settings (Small, Wood, Betteridge, Montaner, & Kerr, 2009). There remain significant barriers to initiating and accessing opioid agonist therapies in custodial settings, and previous research has shown that the majority of individuals with OUD do not have access to MMT while incarcerated (Larney & Dolan, 2009; Bazazi et al, 2017 ; Bozinoff, Small, Long, DeBeck & Fast, 2017). This is particularly concerning given that incarcerated individuals with OUD are at high risk for relapse and fatal overdose in the year post-release, especially in the first month after leaving an incarcerated setting (Binswanger et al, 2007 ; Kinlock et al, 2007 ;Krinsky, Lathrop, Brown, & Nolte, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Project Harapan was a 2×2 multi-factorial randomized controlled trial designed to evaluate and compare the relative effectiveness of a pre-release methadone maintenance program and an evidence-based behavioral intervention (Holistic Health Recovery Program, HHRP+) in terms of reducing HIV-related risk behaviors and illicit drug use for HIV-infected, opioid dependent prisoners in Malaysia [46]. …”
Section: Methodsmentioning
confidence: 99%